It's all in that plate of food: an interview with Carolyn Steel - Salvador, Mariana Sanchez (CIDADES, Comunidades e Territórios, 2020)
Although it might seem that the problem of feeding big cities has been solved, it has come at a heavy cost — ecological destruction, climate crisis, resource depletion, record obesity rates and rising hunger — jeopardizing sustainable development. Furthermore, despite interacting with a number of urban systems, food systems have been disregarded by urban planners until recently, while the distance between consumers and producers increases. Food, however, holds great potential to become the medium through which we pursue a better life and more sustainable cities. In this interview, the British architect Carolyn Steel explores the historical and future connections between humans, cities and food, the current challenges we face in this realm and the possible solutions embedded in her idea of Sitopia — from the Greek words for ‘food’ (sitos) and ‘place’ (topos) — as an approach that could be used to retrofit existing cities, design new ones, and rethink our everyday relationship with the food on our plates.